Plant taxonomy the Universal language - Autrey, Russell; San Luis Video Publishing (Los Osos, California : San Luis Video Publishing, 2002)
This program explains the systems for naming, classifying and identifying plants and also covers many related topics including scientific nomenclature, classification, identification and field botany
pt 1. Understanding plant names (21 min.) - pt 2. Nomenclature and identification (28 min.)
Title from title screen
n.2 is available in VHS format
Executive director, Joe Clokey
Narrator: Deane Harder
Keywords: Plants -- Classification; Plants -- Nomenclature